Production and characterization of alkaliphilic amylases from Bacillus halodurans Alk36 - Mrisho, Latifa Mbwana (Centre for Bioprocess Engineering Research, 2016)
Amylases are hydrolytic enzymes that cause the breakdown of starch and related polysaccharides to simple sugars. Amylases are applied in brewing, food, detergent and textile industries. Most commercial amylases are derived from fungi or bacteria. Bacterial amylases are desired for commercial use, due to their thermo-stability and faster production rates. Bacteria of the genus, Bacillus, are considered to be a good source of extracellular proteins because they have high growth rates and have a naturally high capacity for secretion of extracellular proteins. Bacillus halodurans Alk36 is an alkaliphilic, thermotolerant isolate that can grow over a wide pH and temperature range. Preliminary studies have shown that B. halodurans Alk36 can grown in EnBase® medium (at pH 8.5) containing starch as the carbon source, without the addition of a commercial amylase. The ability to grow on starch, in the absence of an external amylase, indicated that this strain produces endogenous alkaliphilic amylases, which may be exploited for a number of industrial applications. In the present study, the physiological and biochemical characterisation of B. halodurans Alk36 and its endogenous amylases were investigated.